Social stigma and risk determinants associated with tuberculosis transmission to vulnerable residents in India - Anand Prakash Maurya; Neha Mishra; Shashi Ranjan Kumar; Abdul Mabood Khan (International Journal Of Community Medicine And Public Health, 2026)
Due to enduring socioeconomic disparities and deep-rooted societal stigma, tuberculosis (TB) remains one of India's most urgent public health concerns. This review article assesses how societal stigma and important risk factors are linked to the onset and spread of TB, especially in vulnerable groups, including slum dwellers, migrants, and people with little access to healthcare. Stigmatization frequently leads to social isolation, non-adherence to treatment, and delayed diagnosis, all of which raise the risk of ongoing transmission within the community settings. Malnutrition, poverty, and co-infection with HIV increase the vulnerability to infection and the course of the disease. A misconception about TB is that it is an ethically motivated disease that discourages people from seeking treatment through healthcare organisations and reinforces discrimination in many Indian communities. Subsequently, failing to report and insufficient treatment remain major obstacles to controlling this disease. The perceived threat of TB infection transmission among susceptible inhabitants in both urban and rural India is highlighted in this article as a result of these intersecting social and epidemiological factors. Thus, it is imperative to develop stigma-reduction initiatives, integrate TB services into primary healthcare, and strengthen community-based awareness campaigns to break the chains of transmission and assert equal access to healthcare. To achieve India's aim of TB elimination, it is vital to address the combined problem of biological and social risk factors. Knowing the social aspects of TB transmission is essential for developing focused treatments that enhance treatment results and promote a more inclusive, stigma-free public health strategy.